Pengaruh Kecerdasan Intrapersonal Terhadap Kemampuan Pemahaman Konsep Matematika Siswa Sekolah Menengah Atas - Aini, Hanifatul; Khuzaini, Nanang; ., Sustianta (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
This study aims to determine the effect of intrapersonal intelligence on the ability to understand mathematical concepts. The research method used is quantitative research with a correlational survey method. The population in this study were all students of class XII MIPA SMA Negeri 1 Sedayu. The research sample amounted to 65 students taken from 2 XII MIPA classes with sampling techniques using random sampling techniques. Research instruments in the form of intrapersonal intelligence questionnaires and questions about the ability to understand mathematical concepts. The data analysis technique was carried out by classical assumption test and simple regression test. Based on the results of the study obtained that there is a significant positive effect of intrapersonal intelligence on the ability to understand students' mathematical concepts, where the amount of contribution given by intrapersonal intelligence to understanding mathematical concepts is 27.2%.